An inclusive view of Saharan dust advections to Italy and the Central Mediterranean. (15th March 2019) - Gobbi, G.P.; Barnaba, F.; Di Liberto, L.; Bolignano, A.; Lucarelli, F.; Nava, S.; Perrino, C.; Pietrodangelo, A.; Basart, S.; Costabile, F.; Dionisi, D.; Rizza, U.; et al.
Abstract: We address observations of physical and chemical properties of Saharan dust advections (SDA) as observed in the Central Mediterranean basin, within the framework of the LIFE+10, DIAPASON project (www.diapason-life.eu ). DIAPASON aimed at the definition of best practices and tools to detect and evaluate the contribution of Saharan dust to ground particulate matter (PM) loads. Polarization-sensitive, automated lidar-ceilometers (PLC) are one of the tools prototyped and used in the Rome area to reach this goal. The results presented in this study focus on: 1) the effectiveness of various observational tools at detecting and characterizing atmospheric dust plumes, and 2) processes and properties of Saharan dust advections reaching the central Mediterranean region. In this respect, the combination of numerical model forecasts and time-resolved (at least hourly) PLC or chemical observations was found to constitute an efficient way to predict and confirm the presence of Saharan dust. In the period 2011–2014, Saharan dust advections were observed to reach over Rome on about 32% of the days. In some 70% of these days the dust reached the ground in dry conditions, while 30% of advection days involved wet deposition. Dry (wet) deposition was found to maximize (minimize) in summer. The northern Sahara between Algeria and Tunisia (Grand Erg Oriental), was confirmed as the most frequent region of origin of the dust mobilized towards central Italy. Secondary source regions include northern Morocco and Libya. On a statistical basis, Saharan advections to Rome were preceded by increasing atmospheric pressure and stability. These conditions were found to favor the accumulation of aerosols related to local emission sources before the SDA reached the ground. Meteorology (precipitation and turbulence in primis ) resulted to be an important modulator of PM concentrations during SDAs. Magnitude and timing of these factors should be well considered to correctly evaluate the dust share in PM loads or the related health effects. Saharan advections observed during DIAPASON affected particle concentrations down to diameters of about 0.6–1 μm, with number concentrations peaking at the 2.5 μm diameter range. These advections were associated with a significant increase in Si-rich particles containing a non-negligible fraction of water. Rainfall was observed to preferentially remove dust particles larger than 2 μm, causing a significant depletion in the Ca-rich fraction with respect to the Si-rich one. The increase in PLC depolarization ratios above 5%, as well as the hourly PIXE records of the Si/Ca ratio increasing above 1 were found to represent good markers for the actual presence of Saharan dust particulate matter, when Saharan advection conditions are occurring. Highlights: Saharan dust advections to Europe occur some 33% of the time in central Mediterranean. Saharan advections are well identified by polarization lidar and numerical model sinergy. Meteorology is important at modulating dust and pollution properties at receptor sites. Selective wet-removal processes occur within dust-laden, precipitating clouds. Polarization lidar-ceilometers provide optimal 24/7 remote-sensing of atmospheric dust.